Impact of Digital Transformation on Organizational Agility and Business Performance in Medium Sized Enterprise - Ilham, Rachmad; Suwanda, Rian Pramana; Suryaningrum, Ni Made; Wibawa, I Made Landhep (IJBLE Scientific Publications Community Inc., 2026)
This study investigates the impact of digital transformation on organizational agility and business performance in medium-sized enterprises. Using a quantitative research design and survey data collected from managers and employees involved in digital initiatives, the research examines how digital transformation influences agility and contributes to improved organizational outcomes. The findings reveal that digital transformation has a significant positive effect on both organizational agility and business performance, indicating that digital technologies enhance responsiveness, decision-making, and operational efficiency. Moreover, organizational agility is shown to partially mediate the relationship between digital transformation and business performance, suggesting that agility acts as a strategic capability through which technological advancements yield stronger performance benefits. These results underscore the importance of aligning digital transformation initiatives with organizational capabilities and cultivating an agile culture to maximize performance outcomes. The study provides valuable insights for medium-sized enterprises seeking to leverage digital transformation as a driver of competitiveness and long-term sustainability.